(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This study explores the dynamic interplay between emotions and reason in the ethical cultivation frameworks of Ancient Greek and Confucian (Chinese) philosophies. The primary objective is to examine how these two philosophical systems conceptualize emotions and reason, their methods of emotional regulation, and the broader implications for personal development, governance, and social harmony. Additionally, this research addresses the gap in understanding these traditions’ contributions to contemporary discussions on emotional intelligence, leadership, and moral development. The study employs a comparative analysis of primary texts from Confucianism and Greek philosophy, including works by Confucius, Mencius, Plato, and Aristotle. Key concepts such as ren (?, benevolence), li (?, ritual propriety), phronesis (prudence or practical wisdom), and the golden mean (??, zh?ng y?ng) are examined in depth. Confucianism encourages cultivating emotions through social rituals and virtues, focusing on relational harmony. Meanwhile, Greek philosophy stresses the individuals need for self-regulation of emotions through reason, striving for eudaimonia (????, human flourishing). The findings reveal that Confucianism emphasizes relational emotional regulation, while Greek philosophy prioritizes self-control. This comparative analysis provides valuable insights into modern leadership practices and emotional intelligence, demonstrating the enduring influence of these philosophical teachings.